PENGARUH RASIO PENGGUNAAN LIMBAH TERNAK DAN HIJAUAN TERHADAP KUALITAS PUPUK CAIR - Pancapalaga, Wehandaka (Jurnal Gamma, 2011)
Wehandaka PancapalagaStaf Pengajar Jurusan Produksi Ternak, Fakultas Pertanian-Peternakan, Universitas Muhammadiyah MalangAlamat Korespondensi : Vila sengkaling blok p/12MalangEmail: handaka@umm.ac.idABSTRACTOganik fertilizer is not only solid but can also be a liquid such as inorganic fertilizers. Liquidfertilizers seemed more easily utilized by plants as elements in it are not easy to unravel and theamount is too much benefits to be felt sooner. Liquid fertilizer raw materials may come fromsewage Forage and livestock. ratio comparisons and Forage use of livestock waste is will affect thequality of the nutrients contained in liquid manure.This study aimed to determine the origin of waste usage ratio livestock and forage for thecontent of N, P and K fertilizer produced liquid.Research using Completely Randomized Design. As the treatment is the ratio between thewaste and livestock forage. The treatments were as follows P1 = Waste 25% of cattle: Forage 75%P2 = 50% of livestock waste: Forage P3 = 50% Waste 75% of cattle: Forage P4 = 25% and 100%of livestock waste treatment is the respective repeated 3 times. To differentiate the average value ofthe treatment, conducted LSD (Steel and Torric, 1991). While the parameters measured were nitrogencontent, P and K.Conclusion There is a very real effect of the use of livestock waste and forage for the contentof N, P and K fertilizer liquid fertilizer with cair.Untuk Making 100% used livestock waste materialshave content N, P and K high, compared with the other comparisons. content of liquid fertilizerinclude: N at 2.657%, P content of 3.43% and K content of 2.51%